Disability and intersecting statuses - Barnartt, Sharon N.; Altman, Barbara Mandell (Research in social science and disability ;, 2013)
Disability can be either an ascribed status or an achieved status and its combination with other statuses will affect the persons social experiences. The term intersectionality has been used most often to discuss the ways in which the dual and simultaneous statuses of 'black' and ''female' exist as facets of social structure and culture, interact in both those spheres, and affect individuals in ways which neither one does separately. Little attention has been paid to disability in this context, despite the many parallels to race and gender. This volume challenges critical thinking about the interrelationships with disability. It questions if the concepts and methods of intersectionality can be applied to disability at all or if they can be applied in the same way. The authors debate whether different conception of intersectionality would fit the disability context better and if there are methodologies which could be used to examine it. A variety of empirical evidence about situations in which disability intersects with other roles are also examined.